Increasing the Equilibrium Yield of Oxidative Dehydrogenation with CO2 by Secondary Reactions - Müller, Karsten; Baumgärtner, Andrea; Mokrushina, Liudmila; Arlt, Wolfgang (Chemical Engineering & Technology, 2014)
Oxidative dehydrogenation with carbon dioxide as an oxidant at low temperatures is strongly limited by its thermodynamic equilibrium. It is be shown that the equilibrium yield of the desired olefin can significantly be increased utilizing side reactions. This does not necessarily require the addition of another reactant, since this reactant can be formed in situ from the starting alkane. This effect allows for a decrease of the reaction temperature as well as the overall heat demand of the reaction. As a consequence, the exergy demand of the reaction system is reduced substantially.
Keywords: Carbon dioxide; Olefin; Oxidative dehydrogenation; Thermodynamic equilibrium